Academic says demeaning for Dayak women to be paraded in public for Kumang pageants, wants NGOs to reevaluate Gawai event - Edward, Churchill (2024)
A comment on the holding of Kumang Beauty pageant during Gawai Dayak and asked if its time to review this event for in conjunction with Gawai Dayak festival.